Relationship Between Diet And Type 2 Diabetes Militus at Dr. Mamik Clinic - Dedi Supriadi; Siva Khoerun Nisa; Rudi Kurniawan; Henri Setiawan; Dadi Hamdani (LPPM STIKes Muhammadiyah Ciamis, 2020)
Diabetes Mellitus is now a serious threat to humans in the world. One of the factors that cause Diabetes Mellitus is diet. Diabetes Mellitus is a degenerative disease that is closely related to diet. Improper dietary regulation as recommended by 3J (Schedule, Amount, and Type) can result in an increase in blood sugar levels Objective: This study aims to determine the relationship between Diet and Type 2 Diabetes Mellitus at dr. Mamik in 2020. The research method used is a quantitative analysis using a cross-sectional approach. The population in this study were all patients who went to dr. Mamik in May 2020 as many as 142 people. Samples were taken using the quota sampling technique of as many as 59 people. The results of the study show an overview of the diet of patients with type 2 diabetes mellitus at the dr. Mamik, most of whom were in the bad category as many as 40 people (67.8%), a description of the incidence of type 2 diabetes mellitus at the dr. Mamik, the highest frequency was in the category of Type 2 DM as many as 37 people (62.7%) and there was a significant relationship between diet and type 2 diabetes mellitus at Dr. Mamik Clinic because the value of alpha > value. Conclusion: there is a relationship between diet and type 2 diabetes mellitus.